MOUNT PADANG CIANJUR WEST JAVA AS A TOURISM - Tri Agustini Gandaresmi; Yayat Sudaryat; Nunuy Nurjanah (FEBI UIN Sunan Gunung Djati Bandung, 2022)
Mount Padang is one of the mountains in Cianjur, West Java. The purpose of this research is to get to know Mount Padang from the point of view of various aspects. This type of research is qualitative research using library research methods. The type of data used is secondary data which is in the form of journals from previous research. The result of this research is that the tours offered at the Gunung Padang Megalithic Site are the beauty of the terraced punden building composed of volcanic rock columns. The strategy for developing the Gunung Padang cultural heritage site is by: utilizing vacant land around the site area; using promotional media; socialization regarding the preservation of cultural heritage objects; establishing good coordination with management parties regarding aspects of the development of the Gunung Padang cultural heritage site as a tourist destination; regular maintenance of facilities.